Analysis of Serum Markers with Regard to Treatment Procedures in Advanced Stage Prostate Cancer Patients - Wolny-Rokicka, Edyta (Med Sci Monit, 2020)
BACKGROUND: Biomarkers predicting the efficacy of treatment for locally limited prostate cancer are greatly needed. This knowledge could improve the classification of patients for different methods of treatment and enable better recognition of groups with higher risk of biological recurrence. We prospectively assessed serial blood levels of apoptotic biomarkers and correlated them with response to treatment and clinical factors. MATERIAL/METHODS: Blood was collected from 25 patients with prostate cancer before and after surgery, 16 healthy volunteers with benign prostatic hyperplasia (BPH), and 14 patients with metastasized disease. Immunoenzymatic methods were used to determine circulating apoptotic and inflammatory mediators, including tumor necrosis factor α (TNF-α), type I receptor (TNFRI), and type II receptor (TNFRII); FAS ligand (FasL); TNF-related apoptosis-inducing ligand (TRIAL); caspase 8 (Cas8); caspase 9 (Cas9); DNA methylation (metDNA); P-selectin; and high-sensitivity C-reactive protein. The total circulating fragments of cell-free DNA (cfDNA) were measured directly in serum. RESULTS: Peripheral serum prostate-specific antigen increased rapidly together with cfDNA. A negative correlation was noted between tumor volume and TNFRI and TNFRII. Postsurgery P-selectin level was decreased, and metDNA and TNFRII levels were increased. Three comparisons were made between patient groups: surgical vs. BPH; surgical vs. palliative; and palliative vs. BPH. TNFRI, TNFRII, metDNA, P-selectin, Cas8, and FasL were shown to have significant roles. CONCLUSIONS: The study indicated significant roles for cfDNA, both TNF receptors, metDNA, and P-selectin as serum biomarkers in patients with prostate cancer.